RINDU RESERVOIR CHARACTERIZATION: SEQUENCE STRATIGRAPHY, FACIES MODEL AND CORRELATION WITH STEAM DISTRIBUTION IN AREA-10, DURI FIELD - Purwantoko Mahagyo, R
Currently, reservoir characterization is important method in oil industry. It is needed to priority, follow up and future plan in development of oil field economically. The characterization can be generated based on geological condition or production which is correlated with recovery factor. Duri oil field which is the biggest steam flood oil field in Indonesia has applied reservoir characterization both in new area development or area that has been on production for production optimization. Area-10 is part of development area in Duri oil field which is located in the Central Sumatra Basin, and as research area. This area is located in the north of Duri oil field and started development in 2001. Rindu-1_3 and Rindu-5 reservoir are main target for injection and production while Rindu-2, Rindu-3 and Rindu-4 are very thin and are not be developed in this area since not economic. The difference of heat response is very clear. Rindu-5 has more heat compared to Rindu-1 reservoir though this reservoir was injected first. The description of these reservoir is determined using core and facies interpretation that divided become 4 unit (channel, len shale, marine shale and lag/tight) and also apply sequence stratigraphy. Analysis also been done by integrating rock property data especially permeability which is main driver in the steam flood process, and heat distribution can be monitored from well head temperature (WHT) of producer well, temperature log and 4D seismic. By integrating all the data, it can be evaluated to get reservoir characterization and the zone that need more steam injection can be predicted. There will be a strategy to increase steam injection in the bad zone and reduce or maintain steam injection in the good zone.